Octreotide and the mTOR inhibitor RAD001 (everolimus) block proliferation and interact with the Akt-mTOR-p70S6K pathway in a neuro-endocrine tumour cell Line. - Grozinsky-Glasberg, S; Franchi, G; Teng, M; Leontiou, C; Ribeiro de Oliveira, A; Dalino, P; Salahuddin, N; Korbonits, M; Grossman, AB (2008)
BACKGROUND/AIM: The mode of action of the somatostatin analog octreotide on neuro-endocrine tumour proliferation is largely unknown. Overexpression of the proto-oncogene Akt/PKB (protein kinase B) has been demonstrated in certain neuro-endocrine tumours: Akt activates downstream proteins including mTOR and p70S6K, which play an important role in cell proliferation. RAD001 (everolimus) is a novel agent that is being trialled in the treatment of neuro-endocrine tumours, and is known to interact with mTOR. We explored the mechanism of action of octreotide, RAD001, and their combination on cell proliferation and kinase activation in a neuro-endocrine tumour cell line (rat insulinoma cell line, INS1). METHODS: Proliferation assays were used to determine the effects of octreotide, RAD001, and their combination on cell proliferation. Western blotting was used to characterize the expression of phosphorylated Akt, phosphorylated TSC2, phosphorylated mTOR, and phosphorylated 70S6K. RESULTS: Treatment with octreotide and RAD001 inhibited proliferation and attenuated phosphorylation of all downstream targets of Akt: TSC2, mTOR, and p70S6K. CONCLUSIONS: In this cell model, octreotide and RAD001 appear to act through a similar pathway and inhibit the Akt-mTOR-p70S6 kinase pathway downstream of Akt. There may be some overlapping effects of the two inhibitors on the mTOR pathway, although it is likely that other additional effects may differentiate the two agents.